(untitled) (Plant Tissue Culture and Biotechnology, 2017)
In view of the emerging population trends and that wheat crop is the major unequivocally recognized conduit towards addressing the food security challenges of 2050 this discourse embraces various research options that are viewed as possible solutions toward delivering those targets for providing nutritious food and meeting the aspirations that policy setters have debated on the subject for decades. The underlying strength for achieving these targets will require concerted efforts from plant researchers that are well integrated within effectively harnessing and utilizing prevalent genetic diversity of the wide array of alleles in a holistic pro‐active manner. We argue that the purists of basic and strategic research dimensions need to be thoughtfully defined, so that the vital target of delivering the “applied” gains are only realized from the outputs on farmer’s fields and measured by tons per hectare. In this quest, the pre‐breeding disciplines “classical mode” and its recently surfaced “modified sense” are pivotal, where within the former facet “tissue culture” (TC)/artificial culturing is embodied integrally. Taken for granted, TC has been the backbone of all wide hybridization studies and has made an enormous impact on the agricultural landscape spanning over the last six decades. With its intervention significant generic and specific incompatibilities have been overcome as well as allowing researchers to exploit the protocols for adding efficiency to breeding programs, facilitate operational technologies in running breeding programs and development of unique genetic stocks that preserve valuable allelic richness in user friendly forms for future free germplasmusage in global/private domains of plant improvement ventures. Plant Tissue Cult. & Biotech. 27(1): 89-140, 2017 (June)